Perubahan Cara Kerja Akibat Dari Pandemi Global - Hafsyah Yasmita; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2022)
The COVID-19 pandemic, which has hit not only Indonesia but the whole world, certainly affects various sectors, especially the corporate employment system. The implementation of a work system that is usually done conventionally has now turned into a work from home (wfh) system with the concept of working online under the supervision of the company's superiors. People are forced to adapt to new lifestyles that are considered able to reduce their risk of exposure to this disease and in the long term can make them survive in the midst of the epidemic.